An Innovative Selective Laser Melting Process for Hematite‐Doped Aluminum Oxide. Issue 6 (8th March 2019) - Florio, Kevin; Pfeiffer, Stefan; Makowska, Malgorzata; Casati, Nicola; Verga, Fabrizio; Graule, Thomas; Van Swygenhoven, Helena; Wegener, Konrad
Abstract : Selective Laser Melting (SLM) technology is successfully applied to manufacture aluminum oxide parts. The obtained samples are presented and characterized in terms of density, mechanical properties, and structure. The starting material is a powder composed of aluminum oxide granules doped with a small quantity of iron oxide (hematite) as an absorption additive. A green short‐pulsed nanosecond (ns) laser is used in the experimental in‐house designed and built SLM machine. The absorption, reflectance, and transmittance of the starting powder for a laser with wavelength of 532 nm are evaluated using an integrating sphere and it is found that absorption of 68% is sufficient for the established process. Various laser and scanning parameters are studied and a process window is found. Densities above 90% are achieved in the one step process. Bi‐axial flexural strength of 25 MPa in average is recorded in the ball on 3 balls test. Finally, powder diffraction measured in a synchrotron beamline shows the presence of less than 0.6% of hercynite after laser processing. Abstract : A green nanosecond pulsed laser is successfully used for an innovative process of selective laser melting of aluminum oxide. A small quantity (less than 1 wt%) of hematite needs to be added to the granules in order to enhance the absorption of the laser. Dense parts are produced in one single‐step process. The SLM‐produced parts withstand an average of 25 MPa in flexural strength.